2012
DOI: 10.1038/jid.2012.112
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Skin-Specific Inflammation Promotes Vascular Inflammation and Thrombosis

Abstract: Patients with psoriasis have systemic and vascular inflammation and are at increased risk for myocardial infarction, stroke, and cardiovascular death. However, the underlying mechanism(s) mediating the link between psoriasis and vascular disease is incompletely defined. This study sought to determine whether chronic skin-specific inflammation has the capacity to promote vascular inflammation and thrombosis. Using the KC-Tie2 doxycycline-repressible (Dox-off) murine model of psoriasiform skin disease, spontaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
81
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(90 citation statements)
references
References 57 publications
7
81
0
1
Order By: Relevance
“…This phenotype is strikingly similar to common manifestations of human psoriasis, with marked acantosis, hyperkeratosis, and a nucleated cell infiltrate. Furthermore these mice also display severe aortic inflammation, a serious cardiovascular complication observed in some chronic psoriasis suffers (39). These observations highlight the importance of examining IL-1R1-mediated inflammation in psoriasis and further highlight the potential importance of TIR8/SIGIRR as a critical signaling mediator in this context.…”
Section: Discussionmentioning
confidence: 91%
“…This phenotype is strikingly similar to common manifestations of human psoriasis, with marked acantosis, hyperkeratosis, and a nucleated cell infiltrate. Furthermore these mice also display severe aortic inflammation, a serious cardiovascular complication observed in some chronic psoriasis suffers (39). These observations highlight the importance of examining IL-1R1-mediated inflammation in psoriasis and further highlight the potential importance of TIR8/SIGIRR as a critical signaling mediator in this context.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, rare use of topical antibiotic therapy on very severe K14-Rac1V12 -/+ mice may have impacted vascular disease progression. We also did not study patterns of thrombosis in this mouse model, which certainly should be done in the future (7,8). Furthermore, our use of a less-utilized atherosclerosis mouse model (Srb1…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrate that the K14-RacV12 murine model captures the cardiometabolic dysfunction and accelerates vascular disease observed in chronic inflammation and that skin inflammation induces a proatherosclerotic macrophage phenotype with impaired SOD2 function, which associated with accelerated atherogenesis. inflammation in the vasculature (7) and increase thrombosis (8). Recently, Winge et al (9) developed a potentially novel psoriasis mouse model, overexpressing a constitutively active mutant (Rac1 G12V ) of the GTPase Ras-related C3 botulinum toxin substrate 1 (Rac1), in keratinocytes specifically (K14-Rac1V12), resulting in a comparable pathophysiology between human and murine psoriasis spontaneously manifesting as early as 7 days after birth.…”
Section: Introductionmentioning
confidence: 99%
“…Others have suggested a more direct hypothesis that psoriasis-initiated skin and systemic inflammation cause insulin resistance, which promotes endothelial cell dysfunction, subsequent atherosclerosis and ultimately thromboembolic events 7 . It had been demonstrated that sustained skin-specific inflammation promotes inflammation and thrombosis and suggest that aggressive treatment of skin inflammation may attenuate pro-inflammatory and pro-thrombotic pathways that produce thromboembolic events in psoriasis patients 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Clinical data have convincingly demonstrated that psoriasis patients have an increased risk for developing cardiovascular disease and an increased risk of thromboembolic events 2,3 . We report a unique case of a patient who suffered from both psoriasis and subsequent pulmonary embolism (PE).…”
Section: Introductionmentioning
confidence: 99%